ANALISIS LAYANAN GO-FOOD DALAM MENINGKATKAN PENJUALAN PADA UMKM KULINER DI YOGYAKARTA - Singgih Preasetianto; Mahda F. B.; Dimas Martha Kusuma; Agus Dwi Cahya (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2021)
This study aims to identify and analyze natural go-food services to increase culinary sales carried out by GO-JEK in Yogyakarta. This study uses a quantitative approach with a sampling technique using probability sampling. The sample in this study is culinary in Yogyakarta which is done with go-food services. Testing of data instruments in this study uses validity, reliability, and classical assumption tests, while data processing uses simple linear regression. The results showed that the go-food service had a significant and significant effect on increasing culinary sales in Yogyakarta.